Supercapattery performance of MXene-based composite containing HKUST-1 and HKUST-1 derived copper oxide - Ismail, Rashidah (2023)
Sustainable energy storage is very important to fulfil the energy demand and reduce the carbon footprint caused by the combustion of fossil fuels. The selection of materials that have good conductivity, high surface area and electrochemically active is very important to achieve high specific energy and specific power energy storage. Herein, a supercapattery device was fabricated using two promising nanomaterials, MXene and copper-based metal-organic framework known as HKUST-1 (HKUST: Hong Kong University of Science and Technology). Two-dimensional titanium carbide, Ti3C2Tx is a member of MXene that benefits from its conductive layer and electroactive sites with functionalised surface. HKUST-1 is known for its high surface area and highly porous structure that is efficient for electrolyte ion diffusion. The composite of MXene/HKUST-1 was synthesised through ultrasonication. The characterisations of samples were studied through XRD, Raman, BET, and FESEM for their crystallinity, functional groups, surface area, and morphology, respectively. Meanwhile, the specific capacity (Cs) of hybridised MXene/HKUST-1 was evaluated through cyclic voltammetry and galvanostatic charge discharge. The obtained Cs of MXene/HKUST-1 electrode in 1 M LiOH was 201.6 C g-1 at 4 A g-1. MXene/HKUST- 1 (positive electrode) and activated carbon (AC-negative electrode) were assembled into a supercapattery device (MXene/HKUST-1//AC). The device achieved Cs, specific energy (E), and specific power (P) of 53.6 C g-1 at 0.5 A g-1, 11.2 Wh kg-1, and 750 W kg-1, respectively with capacity retention of 94% over 5000 cycles. Subsequently, the electrochemical study was performed on the MXene and HKUST- 1-derived copper oxide (MXene/H-CuO), obtained from the calcination of HKUST-1 at 550°C for 2 hours in the air. The Cs of MXene/H-CuO attained 314 C g-1 at 4 A g-1, whereas the MXene/H-CuO//AC supercapattery device obtained 47.2 C g-1 at 0.4 A g- 1. The E and P for the device were 9.8 Wh kg-1 and 600 W kg-1, respectively. After 5000 cycles, the device retained 74% of its capacity. The remarkable specific capacities and specific energies of the supercapattery devices were contributed by the high surface area of HKUST-1 and the high conductivity of MXene and H-CuO.